Statistical thinking for managers - Hildebrand, David K. (Duxbury Press, 1998)
Data. Summarizing data about one variable. A first look at probability. Random variables and probability distribuitons. Random sampling and sampling distributions. Estimation. Hypothesis testing. Comparing two samples...